The Effect of Providing Education about the Importance of Breastfeeding on the Motivation of Pregnant Women in Preparing to Breastfeed at the Paguat Community Health Center UPTD - Fitriyanti Madina; Anik Sri Purwanti (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Breastfeeding is a crucial practice that provides optimal nutrition and immunity for infants while supporting maternal health. However, inadequate knowledge and limited understanding about the importance of breastfeeding often lead to low motivation among pregnant women in preparing for breastfeeding. Providing structured education is expected improve pregnant women’s readiness and commitment to breastfeeding after childbirth. Objective: This study aimed to determine the effect of providing education about the importance of breastfeeding on the motivation of pregnant women in preparing to breastfeed at the Paguat Community Health Center UPTD. Methods: This study employed a pre-experimental design with one-group pretest–posttest approach. A total of 30 pregnant women were selected as the sample using purposive sampling techniques. Data on mothers’ motivation to prepare for breastfeeding were collected before and after the educational intervention using a structured motivation questionnaire. The data were analyzed using the Wilcoxon signed-rank test to assess differences in motivation levels before and after the intervention. Results: The results of the Wilcoxon signed-rank test showed a p-value of 0.000 (p < 0.05), indicating a statistically significant effect of breastfeeding education on the motivation of pregnant women in preparing breastfeed. The findings demonstrate that educational interventions significantly increased maternal motivation following the provision of education. Conclusion: Providing education about the importance of breastfeeding has a significant positive effect on the motivation of pregnant women in preparing to breastfeed. Therefore, breastfeeding education should be strengthened and routinely implemented during antenatal care services to improve maternal readiness and support successful breastfeeding practices.